(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
Shakespeare’s works, deeply rooted in the sociocultural and historical context of the English Renaissance, present unique challenges for translation into other languages, including Uzbek. This article examines how cultural context influences the translation of Shakespeare’s dramas into Uzbek, focusing on linguistic adaptation, stylistic preservation, and the cultural transference of meaning. The study highlights the difficulties in rendering Elizabethan-era idioms, metaphors, and historical references in a way that resonates with Uzbek audiences. Through comparative analysis, this paper explores different strategies used by translators to maintain the artistic and thematic integrity of Shakespeare’s texts while ensuring their cultural relevance for Uzbek readers. The analysis includes key examples from Hamlet, Macbeth, Othello, and Romeo and Juliet with their respective Uzbek translations, demonstrating the role of cultural adaptation in preserving meaning.